Polyketide synthases from poison hemlock (Conium maculatum L.). (11th September 2015) - Hotti, Hannu; Seppänen‐Laakso, Tuulikki; Arvas, Mikko; Teeri, Teemu H.; Rischer, Heiko
Abstract : Coniine is a toxic alkaloid, the biosynthesis of which is not well understood. A possible route, supported by evidence from labelling experiments, involves a polyketide formed by the condensation of one acetyl‐CoA and three malonyl‐CoAs catalysed by a polyketide synthase (PKS). We isolated PKS genes or their fragments from poison hemlock ( Conium maculatum L.) by using random amplification of cDNA ends (RACE) and transcriptome analysis, and characterized three full‐length enzymes by feeding different starter‐CoAs in vitro . On the basis of our in vitro experiments, two of the three characterized PKS genes in poison hemlock encode chalcone synthases (CPKS1 and CPKS2), and one encodes a novel type of PKS (CPKS5). We show that CPKS5 kinetically favours butyryl‐CoA as a starter‐CoA in vitro . Our results suggest that CPKS5 is responsible for the initiation of coniine biosynthesis by catalysing the synthesis of the carbon backbone from one butyryl‐CoA and two malonyl‐CoAs. Database: Nucleotide sequence data are available in GenBank/EMBL/DDBJ under the accession numbersKP726914, KP726915, KP726916, KP726917, KP726918, andKP726919 Abstract : Coniine is a toxic alkaloid from poison hemlock ( Conium maculatum L.). Biosynthesis involves a polyketide putatively formed by a polyketide synthase (PKS). Three full length genes were expressed and the encoded enzymes characterised by feeding different starter‐CoAs in vitro . A novel PKS favouring butyryl‐CoA as a starter catalyses formation of products with a coniine‐folding mode.